The Pattern of Development of Competence, Commitment, and Motivation of Teachers in Pesantren - Fauzi, Imron; Ubaidillah, Ubaidillah; Indrianto, Nino; Aminulloh, Aminulloh; Asshuwaifiyah, Uwaisah (JURNAL AL-TANZIM, 2022)
This study aims to analyze the development of competence, commitment, and motivation of teachers in the Mu'adah Islamic boarding school. This study used a qualitative method with a multi-case type and was conducted at the Al-Amin Sumenep and Sidogiri Islamic boarding schools, Pasuruan. Data collection techniques used the instruments of the interview, observation, and documentation. Several activities in analyzing data include; data condensation, data presentation, and conclusion drawing. The results of this study found that the development of teacher competence at the Mu' Islamic boarding school is to apply a pattern based on spirituality and professionalism through integrated, holistic, and continuous coaching and training strategies, as well as to cultivate self-taught learning. The development of teacher commitment is based on the principle of devotion because Kyai, coaches, teachers, and students live together and are supported by a religiously nuanced Islamic boarding school environment. The development of teacher motivation is based on the values of sincerity and blessing combined with modern professional management.